Buddhist extremists and Muslim minorities religious conflict in contemporary Sri Lanka - Holt, John (Oxford University Press, 2016)
The rise of right-wing groups of Sinhala Buddhists in Sri Lanka in recent years has caused a new wave of religious violence, in this case with Muslims being the primary targets.